Physicochemical and bacteriological analysis of Binog Creek water in Palo, Leyte - Ligason, Weimela M.; Mallonga, Zoe K. (2024)
Bacterial contamination in environmental waters has been an issue in the Philippines due to rapid industrialization and urbanization. Understanding the sources and implications of total and fecal coliform contamination is crucial for managing and protecting water resources for human and environmental health. This study aimed to evaluate the presence of bacterial communities and determine the physicochemical parameters of five selected areas namely (1) downstream, (2) commercial, (3) non- residential, (4) upstream, and (5) residential of Binog Creek in Palo, Leyte. Using the Most Probable Number technique, TC and FC were quantified in water samples and compared to the DENR water quality standards. Results showed all samples were beyond the standard MPN/100mL values, with the highest TC and FC levels in samples 1 and 2. Physicochemical analysis revealed acceptable temperature and pH levels, salinity indicating freshwater-seawater mixing, high turbidity in commercial areas, and low dissolved oxygen levels in all samples. High coliform levels, particularly in downstream and commercial areas, underscore the need for urgent interventions to improve water quality and raise public awareness.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.